High-strength carbon ceramic brake disc and preparation method thereof
By using resin impregnation and chopping carbon fibers in the preparation of carbon ceramic brake discs, and adding CVI deposited fibers to the matrix, the problem of insufficient strength and toughness of carbon ceramic brake discs is solved, achieving high strength and low cost Material properties.
Patent Information
- Application Number
- CN202411511164.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-28
AI Technical Summary
The carbon ceramic brake discs are insufficient in strength and toughness after CVI treatment, especially during short chopping and pressing, fibers are easily destroyed, resulting in a decrease in product strength.
The preparation method of high-strength carbon ceramic brake disc is adopted to reduce fiber damage by impregnating resin and chopping carbon fibers, and the fibers deposited by CVI are added to the matrix to exert toughening effect by using the deposition carbon/carbon fiber interface.
Improves the strength and toughness of the brake disc, reduces material costs, and solves the damage to the fibers during chopping and pressing.
Smart Images

Figure BDA0005105511340000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of brake disc manufacturing, and in particular to a high-strength carbon ceramic brake disc and a preparation method thereof. Background Art
[0002] The brake disc is an important component installed on vehicles such as cars and motorcycles for braking. It is usually located between the wheels and works with the brake caliper, brake pads, etc. in the brake system. The brake disc is part of the automobile braking system. In addition to the brake disc, the disc brake also has calipers, brake pads, brake pipes and other parts. The brake disc rotates with the wheel. The brake pad is installed inside the caliper and remains stationary relative to the brake disc. When the driver steps on the brake, the brake oil in the brake pipe acts as a hydraulic medium to apply pressure to the piston in the caliper, so that the brake pad holds the brake disc tightly, and the friction force stops the brake disc from rotating, thereby playing a role in deceleration or parking. The types of brake discs can be divided into three types according to the material. Gray cast iron, carbon-carbon and carbon-ceramic brake discs. As a new type of brake material, carbon-ceramic brake material has the advantages of low density, stable friction coefficient, large braking ratio, no corrosion and long service life compared with traditional metal and semi-metal brake materials, especially no thermal decay when braking continuously for a long time. It has a wide range of application prospects in the braking field of high-speed trains, cars, airplanes, etc. At present, the preparation process of carbon ceramic brake discs is divided into long fiber process and short fiber process. In the short fiber process, the carbon fiber is firstly CVI deposited for protection, and then the deposited fiber is chopped, mixed with resin and corresponding additives, and then obtained by carbonization and siliconization. The deposited carbon of CVI has a good protective effect on the carbon fiber, but it is easy to damage the fiber when chopped, and the pressing pressure during hot pressing will also damage the CVI fiber, causing the fiber to be divided into multiple bundles. When siliconizing, the fiber is prone to corrosion by silicon, resulting in a decrease in product strength.
[0003] Therefore, a high-strength carbon ceramic brake disc is proposed to address the problem that chemical vapor deposited carbon fibers are easily damaged during chopping and pressing, reduce the damage to the fiber bundles during chopping and pressing, and improve the strength and toughness of the material. Summary of the invention
[0004] The present invention aims to provide a high-strength carbon ceramic brake disc to solve the problem of insufficient strength and toughness of the brake disc after CVI treatment.
[0005] To achieve this purpose, the present invention provides a high-strength carbon ceramic brake disc, which contains 40-60 vol% carbon, 30-55 vol% silicon carbide and 3-13 vol% silicon. The carbon includes a resin carbon fiber phase and a deposited carbon fiber phase, and the resin carbon fiber phase includes resin carbon and a skeleton carbon fiber coated with resin carbon. The deposited carbon fiber phase includes deposited carbon and filled carbon fibers coated with deposited carbon; the content of the resin carbon fiber phase is 35-55%, and the content of the deposited carbon fiber phase is 3-15%.
[0006] Preferably, the content of skeleton carbon fiber in the resin carbon fiber phase is 40-60%, the content of resin carbon is 40-60%, and the extinction angle of resin carbon is less than 18°.
[0007] Preferably, the content of filled carbon fibers in the deposited carbon fiber phase is 35-55%, the content of deposited carbon is 45-65%, and the extinction angle of the deposited carbon is greater than 18°.
[0008] Preferably, the k value of the skeleton carbon fiber is 3-12k, and the k value of the filling carbon fiber is 0.3-3k.
[0009] Preferably, the length of the skeleton carbon fiber is 6-15 mm, and the length of the filling carbon fiber is 5-13 mm.
[0010] Preferably, the skeleton carbon fiber in the resin carbon fiber phase has a plurality of grooves parallel to the length direction of the fiber, and the depth of the grooves is 0.05-1 μm.
[0011] The present invention also provides a method for preparing a high-strength carbon ceramic brake disc, which is used for the above-mentioned high-strength carbon ceramic brake disc. The preparation method is as follows:
[0012] S1: oxidizing 3-12k carbon fiber to remove the sizing agent on the surface to obtain oxidized carbon fiber, wherein the oxidation treatment is carried out by soaking in concentrated nitric acid or heating in air atmosphere;
[0013] S2: impregnating the oxidized carbon fiber with resin to obtain pre-impregnated carbon fiber, wherein the volume of the resin after impregnation is 57-75% of the total volume of the resin and the oxidized carbon fiber;
[0014] S3: chopping the prepreg carbon fiber into short pieces, wherein the length of the short pieces is 6-15 mm, to obtain short-cut prepreg carbon fiber;
[0015] S4: performing CVI deposition on 0.3-3k carbon fibers to obtain deposited long carbon fibers, wherein the deposited long carbon fibers have a carbon fiber content of 35-55% and a deposited carbon content of 45-65%;
[0016] S5: chopping the deposited long carbon fiber to obtain deposited short carbon fiber with a length of 5-13 mm;
[0017] S6: Mix the deposited short carbon fiber, the chopped prepreg carbon fiber and the phenolic resin in a certain proportion to obtain a mixture, put the mixture into a mold for pressing and curing to obtain a preform, the pressure is 20-30MPa, the temperature is 120-160°C, and the temperature is kept for 3-4h;
[0018] S7: Carbonizing the preform to obtain a carbonized body, the carbonization temperature is 800-1200° C., and the temperature is kept for 2-6 hours;
[0019] S8: machining the carbide to obtain a brake disc blank, and then placing the brake disc blank into a boron nitride crucible;
[0020] S9: placing the boron nitride crucible containing the brake disc blank into a siliconizing furnace for siliconizing treatment, and performing surface grinding and outer contour dimension processing after the siliconizing treatment to obtain the high-strength carbon ceramic brake disc.
[0021] Preferably, the mixture in step S6 contains 4-17 vol% of deposited short carbon fibers, 40-65 vol% of chopped prepreg carbon fibers, and the remainder is phenolic resin.
[0022] Preferably, silicon powder having a mass 1.1 times that of the brake disc blank is pre-placed in the boron nitride crucible.
[0023] Preferably, the siliconizing treatment temperature is 1600-1800°C, the holding time is 2-6h, and the furnace pressure is less than 1000Pa.
[0024] Beneficial effects: The present invention provides a high-strength carbon ceramic brake disc, which contains a certain proportion of resin carbon fiber phase and deposited carbon fiber phase in the matrix. Aiming at the problem that chemical vapor deposited carbon fiber is easily damaged during chopped and pressed, the carbon of the high-strength carbon ceramic brake disc is mainly resin carbon fiber phase, and the fiber is impregnated with resin and solidified before being chopped. The resin carbon fiber phase is protected by resin during chopped and impregnated, and the fiber damage is less, which effectively improves the strength of the brake disc; the present invention also adds some filling fibers that have been chemically vapor deposited but have a smaller fiber bundle k value in the matrix. The deposited carbon fiber phase can play its role in deflecting cracks in the product due to the presence of the interface of deposited carbon / carbon fiber, which ensures the toughness of the material and can solve the problem that the fiber impregnated with resin alone has a strong bonding force between the resin carbon and the carbon fiber after carbonization, which causes the toughness of the brake disc to decrease. At the same time, because the proportion of the resin carbon fiber phase in the brake disc is relatively large and the proportion of the deposited carbon fiber phase is relatively small, the skeleton carbon fiber in the resin carbon fiber phase does not need to be treated with CVI, which can greatly reduce the preparation cost. The present invention also proposes a method for preparing a high-strength carbon-ceramic brake disc, which uses short fiber bundles treated in two different ways to reinforce the matrix. The resin carbon fiber phase is protected by the resin during chopping and impregnation, so the fiber damage is less, ensuring the strength of the material; and the deposited carbon fiber phase has an interface between deposited carbon / carbon fiber, which improves the toughness of the material. Compared with direct impregnation with resin, the sizing agent on the fiber surface is removed before impregnation, which reduces the bonding strength between the resin carbon and the carbon fiber, and also helps to improve the toughness of the material. Most of the fibers use the resin carbon fiber phase, which reduces the amount of CVI to protect the carbon fiber and effectively reduces the material cost. DETAILED DESCRIPTION
[0025] The embodiments described below are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] The present invention provides a high-strength carbon ceramic brake disc, which contains 40-60vol% carbon, 30-55vol% silicon carbide and 3-13vol% silicon. For example, the high-strength carbon ceramic brake disc contains 50vol% carbon, 45vol% silicon carbide and 5vol% silicon; or the high-strength carbon ceramic brake disc contains 55vol% carbon, 42vol% silicon carbide and 3vol% silicon; or the high-strength carbon ceramic brake disc contains 45vol% carbon, 50vol% silicon carbide and 5vol% silicon, etc. The carbon includes a resin carbon fiber phase and a deposited carbon fiber phase, and the resin carbon fiber phase includes resin carbon and a skeleton carbon fiber coated with resin carbon. The deposited carbon fiber phase includes deposited carbon and filled carbon fibers coated with deposited carbon; the content of the resin carbon fiber phase is 35-55%, and the content of the deposited carbon fiber phase is 3-15%.
[0027] The content of skeleton carbon fiber in the resin carbon fiber phase is 40-60%, the content of resin carbon is 40-60%, and the extinction angle of resin carbon is less than 18°. The small extinction angle of resin carbon indicates that the carbon atoms are in a disordered arrangement state at the microscopic level, and the rigidity is high, and the interface bonding force with carbon fiber is good.
[0028] The content of filled carbon fibers in the deposited carbon fiber phase is 35-55%, the content of deposited carbon is 45-65%, and the extinction angle of the deposited carbon is greater than 18°. The large extinction angle of the deposited carbon indicates that its carbon atoms are arranged in an orderly manner, close to the layered structure of graphite, the rigidity of the deposited carbon is low, and the bonding force between the deposited carbon and the carbon fibers is weak, which is beneficial to the peeling of the deposited carbon / carbon fiber interface and exerts its toughening effect through weak interface deflection.
[0029] The k value of the skeleton carbon fiber is 3-12k, and the k value of the filling carbon fiber is 0.3-3k.
[0030] The length of the skeleton carbon fiber is 6-15 mm, and the length of the filling carbon fiber is 5-13 mm.
[0031] The skeleton carbon fiber in the resin carbon fiber phase has a plurality of grooves parallel to the length direction of the fiber, and the depth of the grooves is 0.05-1 μm.
[0032] The present invention also provides a method for preparing a high-strength carbon ceramic brake disc, which is used for the above-mentioned high-strength carbon ceramic brake disc. The preparation method is as follows:
[0033] S1: oxidizing 3-12k carbon fiber to remove the sizing agent on the surface to obtain oxidized carbon fiber, wherein the oxidation treatment is carried out by soaking in concentrated nitric acid or heating in air atmosphere;
[0034] S2: impregnating the oxidized carbon fiber with resin to obtain pre-impregnated carbon fiber, wherein the volume of the resin after impregnation is 57-75% of the total volume of the resin and the oxidized carbon fiber;
[0035] S3: chopping the prepreg carbon fiber into short pieces, wherein the length of the short pieces is 6-15 mm, to obtain short-cut prepreg carbon fiber;
[0036] S4: performing CVI deposition on 0.3-3k carbon fibers to obtain deposited long carbon fibers, wherein the deposited long carbon fibers have a carbon fiber content of 35-55% and a deposited carbon content of 45-65%;
[0037] S5: chopping the deposited long carbon fiber to obtain deposited short carbon fiber with a length of 5-13 mm;
[0038] S6: Mix the deposited short carbon fiber, the chopped prepreg carbon fiber and the phenolic resin in a certain proportion to obtain a mixture, put the mixture into a mold for pressing and curing to obtain a preform, the pressure is 20-30MPa, the temperature is 120-160°C, and the temperature is kept for 3-4h;
[0039] S7: Carbonizing the preform to obtain a carbonized body, the carbonization temperature is 800-1200° C., and the temperature is kept for 2-6 hours;
[0040] S8: machining the carbide to obtain a brake disc blank, and then placing the brake disc blank into a boron nitride crucible;
[0041] S9: placing the boron nitride crucible containing the brake disc blank into a siliconizing furnace for siliconizing treatment, and performing surface grinding and outer contour dimension processing after the siliconizing treatment to obtain the high-strength carbon ceramic brake disc.
[0042] The mixture in step S6 contains 4-17 vol% of deposited short carbon fibers, 40-65 vol% of chopped pre-impregnated carbon fibers, and the remainder is phenolic resin.
[0043] Silicon powder with a mass 1.1 times that of the brake disc blank is placed in advance in the boron nitride crucible.
[0044] The siliconizing treatment temperature is 1600-1800°C, the holding time is 2-6h, and the furnace pressure is less than 1000Pa.
[0045] Example 1
[0046] This embodiment provides a high-strength carbon ceramic brake disc, and the preparation steps are as follows:
[0047] S1: 6k carbon fiber is subjected to oxidation treatment to remove the sizing agent on the surface to obtain oxidized carbon fiber, wherein the oxidation treatment is carried out by soaking in concentrated nitric acid;
[0048] S2: impregnating the oxidized carbon fiber with resin to obtain pre-impregnated carbon fiber, wherein the volume of the resin after impregnation is 60% of the total volume of the resin and the oxidized carbon fiber;
[0049] S3: chopping the prepreg carbon fiber into short pieces, wherein the length of the short pieces is 10 mm, to obtain short-cut prepreg carbon fiber;
[0050] S4: performing CVI deposition on 1k carbon fiber to obtain deposited long carbon fiber, wherein the deposited long carbon fiber has a carbon fiber content of 50% and a deposited carbon content of 50%;
[0051] S5: chopping the deposited long carbon fiber to obtain deposited short carbon fiber with a length of 7 mm;
[0052] S6: Mixing the deposited short carbon fibers, chopped prepreg carbon fibers and phenolic resin in a certain proportion to obtain a mixture, wherein the mixture contains 10 vol% of the deposited short carbon fibers, 60 vol% of the chopped prepreg carbon fibers and the remainder is phenolic resin; placing the mixture into a mold for pressing and curing to obtain a preform, the pressure is 20 MPa, the temperature is 130° C., and the temperature is kept for 3 hours;
[0053] S7: Carbonizing the preform to obtain a carbonized body at a carbonization temperature of 900° C. for 5 hours;
[0054] S8: machining the carbide to obtain a brake disc blank, and then placing the brake disc blank into a boron nitride crucible, wherein silicon powder having a mass of 1.1 times that of the brake disc blank is pre-placed in the boron nitride crucible;
[0055] S9: placing the boron nitride crucible containing the brake disc blank into a siliconizing furnace for siliconizing treatment, wherein the siliconizing treatment temperature is 1700° C., the holding time is 3 hours, and the furnace pressure is less than 1000 Pa; after the siliconizing treatment, surface grinding and outer contour dimension processing are performed to obtain the high-strength carbon ceramic brake disc.
[0056] Example 2
[0057] This embodiment provides a high-strength carbon ceramic brake disc, and the preparation steps are as follows:
[0058] S1: 3k carbon fiber is subjected to oxidation treatment to remove the sizing agent on the surface to obtain oxidized carbon fiber, wherein the oxidation treatment is carried out by soaking in concentrated nitric acid;
[0059] S2: impregnating the oxidized carbon fiber with resin to obtain pre-impregnated carbon fiber, wherein the volume of the resin after impregnation is 60% of the total volume of the resin and the oxidized carbon fiber;
[0060] S3: chopping the prepreg carbon fiber into short pieces, wherein the length of the short pieces is 10 mm, to obtain short-cut prepreg carbon fiber;
[0061] S4: performing CVI deposition on 1k carbon fiber to obtain deposited long carbon fiber, wherein the deposited long carbon fiber has a carbon fiber content of 50% and a deposited carbon content of 50%;
[0062] S5: chopping the deposited long carbon fiber to obtain deposited short carbon fiber with a length of 7 mm;
[0063] S6: Mixing the deposited short carbon fibers, chopped prepreg carbon fibers and phenolic resin in a certain proportion to obtain a mixture, wherein the mixture contains 10 vol% of the deposited short carbon fibers, 60 vol% of the chopped prepreg carbon fibers and the remainder is phenolic resin; placing the mixture into a mold for pressing and curing to obtain a preform, the pressure is 20 MPa, the temperature is 130° C., and the temperature is kept for 3 hours;
[0064] S7: Carbonizing the preform to obtain a carbonized body at a carbonization temperature of 900° C. for 5 hours;
[0065] S8: machining the carbide to obtain a brake disc blank, and then placing the brake disc blank into a boron nitride crucible, wherein silicon powder having a mass of 1.1 times that of the brake disc blank is pre-placed in the boron nitride crucible;
[0066] S9: placing the boron nitride crucible containing the brake disc blank into a siliconizing furnace for siliconizing treatment, wherein the siliconizing treatment temperature is 1700° C., the holding time is 3 hours, and the furnace pressure is less than 1000 Pa; after the siliconizing treatment, surface grinding and outer contour dimension processing are performed to obtain the high-strength carbon ceramic brake disc.
[0067] Example 3
[0068] This embodiment provides a high-strength carbon ceramic brake disc, and the preparation steps are as follows:
[0069] S1: 6k carbon fiber is subjected to oxidation treatment to remove the sizing agent on the surface to obtain oxidized carbon fiber, wherein the oxidation treatment is carried out by soaking in concentrated nitric acid;
[0070] S2: impregnating the oxidized carbon fiber with resin to obtain pre-impregnated carbon fiber, wherein the volume of the resin after impregnation is 60% of the total volume of the resin and the oxidized carbon fiber;
[0071] S3: chopping the prepreg carbon fiber into short pieces, wherein the length of the short pieces is 10 mm, to obtain short-cut prepreg carbon fiber;
[0072] S4: performing CVI deposition on 1k carbon fiber to obtain deposited long carbon fiber, wherein the deposited long carbon fiber has a carbon fiber content of 50% and a deposited carbon content of 50%;
[0073] S5: chopping the deposited long carbon fiber to obtain deposited short carbon fiber with a length of 7 mm;
[0074] S6: Mixing the deposited short carbon fibers, chopped prepreg carbon fibers and phenolic resin in a certain proportion to obtain a mixture, wherein the mixture contains 13 vol% of the deposited short carbon fibers, 65 vol% of the chopped prepreg carbon fibers and the remainder is phenolic resin; placing the mixture into a mold for pressing and curing to obtain a preform, the pressure is 20 MPa, the temperature is 130° C., and the temperature is kept for 3 hours;
[0075] S7: Carbonizing the preform to obtain a carbonized body at a carbonization temperature of 900° C. for 5 hours;
[0076] S8: machining the carbide to obtain a brake disc blank, and then placing the brake disc blank into a boron nitride crucible, wherein silicon powder having a mass of 1.1 times that of the brake disc blank is pre-placed in the boron nitride crucible;
[0077] S9: placing the boron nitride crucible containing the brake disc blank into a siliconizing furnace for siliconizing treatment, wherein the siliconizing treatment temperature is 1700° C., the holding time is 3 hours, and the furnace pressure is less than 1000 Pa; after the siliconizing treatment, surface grinding and outer contour dimension processing are performed to obtain the high-strength carbon ceramic brake disc.
[0078] Comparative Example 1
[0079] This comparative example provides a carbon ceramic brake disc, and the preparation steps are as follows:
[0080] S1: 6k carbon fiber is impregnated with resin to obtain pre-impregnated carbon fiber, and the volume of the resin after impregnation is 60% of the total volume of the resin and the oxidized carbon fiber;
[0081] S2: chopping the prepreg carbon fiber into short pieces, wherein the length of the short pieces is 10 mm, to obtain short-cut prepreg carbon fiber;
[0082] S3: performing CVI deposition on 1k carbon fiber to obtain deposited long carbon fiber, wherein the deposited long carbon fiber has a carbon fiber content of 50% and a deposited carbon content of 50%;
[0083] S4: chopping the deposited long carbon fiber to obtain deposited short carbon fiber with a length of 7 mm;
[0084] S5: mixing the deposited short carbon fiber, the chopped prepreg carbon fiber and the phenolic resin in a certain proportion to obtain a mixture, wherein the mixture contains 10 vol% of the deposited short carbon fiber, 60 vol% of the chopped prepreg carbon fiber and the balance is phenolic resin; placing the mixture into a mold for pressing and curing to obtain a preform, the pressure is 20 MPa, the temperature is 130° C., and the temperature is kept for 3 hours;
[0085] S6: carbonizing the preform to obtain a carbonized body at a carbonization temperature of 900° C. for 5 hours;
[0086] S7: machining the carbide to obtain a brake disc blank, and then placing the brake disc blank into a boron nitride crucible, wherein silicon powder having a mass of 1.1 times that of the brake disc blank is pre-placed in the boron nitride crucible;
[0087] S8: placing the boron nitride crucible containing the brake disc blank into a siliconizing furnace for siliconizing treatment, wherein the siliconizing treatment temperature is 1700° C., the holding time is 3 hours, and the furnace pressure is less than 1000 Pa; after the siliconizing treatment, surface grinding and outer contour dimension processing are performed to obtain the carbon ceramic brake disc.
[0088] Comparative Example 2
[0089] This comparative example provides a carbon ceramic brake disc, and the preparation steps are as follows:
[0090] S1: CVI deposition of 6k carbon fiber to obtain deposited long carbon fiber, wherein the deposited long carbon fiber has a carbon fiber content of 50% and a deposited carbon content of 50%;
[0091] S2: chopping the deposited long carbon fiber to obtain deposited short carbon fiber with a length of 7 mm;
[0092] S3: Mixing the deposited short carbon fibers and phenolic resin in a certain proportion to obtain a mixture, wherein the mixture contains 70 vol% of the deposited short carbon fibers and the remainder is phenolic resin; placing the mixture into a mold for pressing and curing to obtain a preform, the pressure is 20 MPa, the temperature is 130° C., and the temperature is kept for 3 hours;
[0093] S4: carbonizing the preform to obtain a carbonized body at a carbonization temperature of 900° C. for 5 hours;
[0094] S5: machining the carbide to obtain a brake disc blank, and then placing the brake disc blank into a boron nitride crucible, wherein silicon powder having a mass of 1.1 times that of the brake disc blank is pre-placed in the boron nitride crucible;
[0095] S6: placing the boron nitride crucible containing the brake disc blank into a siliconizing furnace for siliconizing treatment, wherein the siliconizing treatment temperature is 1700° C., the holding time is 3 hours, and the furnace pressure is less than 1000 Pa; after the siliconizing treatment, surface grinding and outer contour dimension processing are performed to obtain the high-strength carbon ceramic brake disc.
[0096] The brake discs prepared in the above-mentioned Examples 1-3 and Comparative Examples 1-2 were tested. The test method is:
[0097] The impact toughness was tested using the GBT_14389-1993 engineering ceramics impact toughness test method.
[0098] The bending strength is tested using the GBT_65669-2006 fine ceramic bending strength test method.
[0099] The extinction angle was tested using a polarizing microscope.
[0100] The test data is shown in Table 1.
[0101] Table 1 Brake disc test data of Examples 1-3 and Comparative Examples 1-2
[0102]
[0103] From the above test data, it can be seen from Example 1 that the strength of the composite material prepared by this scheme reaches 125MPa, which meets the material performance requirements of the composite carbon ceramic disc; Example 2 changes the fiber to 3k and 1k fiber composite, the interface of carbon fiber / matrix becomes more, and the toughness of the material becomes greater, but due to the increase in the contact area between the fiber and silicon during siliconization, the amount of silicon carbide produced by the fiber reaction increases, and the strength decreases to a certain extent, but is still greater than 110MPa; Example 3 increases the amount of fiber added, and the strength and toughness of the material are improved after siliconization.
[0104] In comparative example 1, the fiber has not been oxidized, resulting in a strong bond between the fiber and the resin carbon. The fiber is not prone to interface separation when it breaks, resulting in brittle fracture of the stress-concentrated fiber, and the toughness of the material is reduced. After the fiber is oxidized, the surface grooves originally covered by the sizing agent are exposed again. Therefore, in the final product, there will be grooves distributed along the length direction on the fiber surface of the resin carbon fiber phase. The fiber is first oxidized to remove the sizing agent on the surface of the carbon fiber, and many grooves will appear on the carbon fiber (the carbon fiber itself has grooves on the surface, but these grooves will be covered after being treated with the sizing agent). There are two purposes for removing this layer of sizing agent: 1. The sizing agent is not resistant to high temperatures, and after carbonization, a gap will be formed between the resin carbon and the carbon fiber, resulting in poor bonding between the carbon fiber and the resin carbon; 2. After removing the sizing agent, grooves will appear on the fiber surface, and these grooves will increase the bonding between the carbon fiber and the resin carbon. The grooves can increase the bonding between the carbon fiber and the resin carbon, increase the strength of the sample, but the toughness will decrease. In the present invention, toughness is provided by CVI carbon / carbon fiber, and better comprehensive performance is achieved by compounding two carbon fibers with different properties. In Example 2, the fibers are all CVI fibers. During the preparation process, the carbon fibers are easily damaged. The 6k fibers may become fibers with a very low k value, resulting in a large contact area between the fibers and silicon, severe fiber corrosion, and a decrease in the mechanical properties of the material.
[0105] The above disclosures are only several preferred embodiments of the present invention, which certainly cannot be used to limit the scope of rights of the present invention. Therefore, equivalent changes made according to the scope of the patent application of the present invention are still within the scope covered by the present invention.
Claims
1. A high-strength carbon ceramic brake disc, characterized in that: The high-strength carbon-ceramic brake disc contains 40-60 vol% carbon, 30-55 vol% silicon carbide and 3-13 vol% silicon; the carbon includes a resin carbon fiber phase and a deposited carbon fiber phase, the resin carbon fiber phase includes resin carbon and a skeleton carbon fiber coated with resin carbon; the deposited carbon fiber phase includes deposited carbon and filled carbon fibers coated with deposited carbon; the content of the resin carbon fiber phase is 35-55%, and the content of the deposited carbon fiber phase is 3-15%.
2. The high-strength carbon ceramic brake disc according to claim 1, characterized in that: The content of skeleton carbon fiber in the resin carbon fiber phase is 40-60%, the content of resin carbon is 40-60%, and the extinction angle of the resin carbon is less than 18°.
3. The high-strength carbon ceramic brake disc according to claim 1, characterized in that: The content of filled carbon fibers in the deposited carbon fiber phase is 35-55%, the content of deposited carbon is 45-65%, and the extinction angle of the deposited carbon is greater than 18°.
4. The high-strength carbon ceramic brake disc according to claim 1, characterized in that: The k value of the skeleton carbon fiber is 3-12k, and the k value of the filling carbon fiber is 0.3-3k.
5. The high-strength carbon ceramic brake disc according to claim 4, characterized in that: The length of the skeleton carbon fiber is 6-15 mm, and the length of the filling carbon fiber is 5-13 mm.
6. The high-strength carbon ceramic brake disc according to claim 1, characterized in that: The skeleton carbon fiber in the resin carbon fiber phase has a plurality of grooves parallel to the length direction of the fiber, and the depth of the grooves is 0.05-1 μm.
7. A method for preparing a high-strength carbon-ceramic brake disc, used for preparing a high-strength carbon-ceramic brake disc as claimed in any one of claims 1 to 5, characterized in that: The preparation method is as follows: S1: oxidizing 3-12k carbon fiber to remove the sizing agent on the surface to obtain oxidized carbon fiber, wherein the oxidation treatment is carried out by soaking in concentrated nitric acid or heating in air atmosphere; S2: impregnating the oxidized carbon fiber with resin to obtain pre-impregnated carbon fiber, wherein the volume of the resin after impregnation is 57-75% of the total volume of the resin and the oxidized carbon fiber; S3: chopping the prepreg carbon fiber into short pieces, wherein the length of the short pieces is 6-15 mm, to obtain short-cut prepreg carbon fiber; S4: performing CVI deposition on 0.3-3k carbon fibers to obtain deposited long carbon fibers, wherein the deposited long carbon fibers have a carbon fiber content of 35-55% and a deposited carbon content of 45-65%; S5: chopping the deposited long carbon fiber to obtain deposited short carbon fiber with a length of 5-13 mm; S6: Mix the deposited short carbon fiber, the chopped prepreg carbon fiber and the phenolic resin in a certain proportion to obtain a mixture, put the mixture into a mold for pressing and curing to obtain a preform, the pressure is 20-30MPa, the temperature is 120-160°C, and the temperature is kept for 3-4h; S7: Carbonizing the preform to obtain a carbonized body, the carbonization temperature is 800-1200° C., and the temperature is kept for 2-6 hours; S8: machining the carbide to obtain a brake disc blank, and then placing the brake disc blank into a boron nitride crucible; S9: placing the boron nitride crucible containing the brake disc blank into a siliconizing furnace for siliconizing treatment, and performing surface grinding and outer contour dimension processing after the siliconizing treatment to obtain the high-strength carbon ceramic brake disc.
8. The method for preparing a high-strength carbon ceramic brake disc according to claim 7, characterized in that: In step S6, the mixture contains 4-17 vol% of deposited short carbon fibers, 40-65 vol% of chopped prepreg carbon fibers, and the remainder is phenolic resin.
9. The method for preparing a high-strength carbon ceramic brake disc according to claim 7, characterized in that: Silicon powder with a mass 1.1 times that of the brake disc blank is placed in advance in the boron nitride crucible.
10. The method for preparing a high-strength carbon ceramic brake disc according to claim 7, characterized in that: The siliconizing treatment temperature is 1600-1800°C, the holding time is 2-6h, and the furnace pressure is less than 1000Pa.
Citation Information
Patent Citations
Carbon-ceramic composite brake disc and preparation method thereof
CN103553695A
High-strength and high-toughness carbon ceramic brake disc and preparation method thereof
CN117962432A
Preparation method of high-strength carbon-ceramic brake disc and product
CN118459225A
Carbon-ceramic brake disc with matrix containing short carbon fibers and preparation method of carbon-ceramic brake disc
CN118479885A
Method for preparing carbon-ceramic brake material and method for preparing carbon-ceramic brake disc
WO2017107735A1
Cited By
Molded carbon-ceramic brake disc and preparation method and application thereof
CN120817814A
A molded carbon-ceramic brake disc and a preparation method and application thereof
CN120817814B